PENENTUAN HARGA JUAL MINIMUM ANDESIT MENGGUNAKAN METODE BREAK EVEN POINT DAN NET ANNUAL VALUE PADA PT. PRO INTERTECH INDONESIA - Juanita R. Horman (INTAN Jurnal Penelitian Tambang, 2019)
The recent increased development indirectly has an implication to the increase of the need of gravel materials. Thus, management efforts should be importantly implemented in mining operations, particularly Andesite. To run a new mining operation, an analysis regarding finance planning would be needed in order to determine the minimum selling price, so that the company was avoided from losses. The calculation method used to determine the selling price is Break Even Point and Net Annual Value. Break Even Point is a point or a condition where a company does not make profit and does not suffer losses. In other words, in that situation, the profit and the losses are zero. Meanwhile, Net Annual Value is used to calculate the amount of money that is the same value each year (during the life of the project) in which the value is equivalent to money value throughout the life of the project, at certain rate of return on capital (ith). According to the calculation, the Break Even Point of the operation is Rp. 19,898,009,014 (capital cost). The minimum selling price of andesite is Rp. 411,964.88/m3. Whereas, using Net Annual Value at 12.75% interest rate, the selling price of Andesite would be Rp. 284,224.15/m3 throughout 14 years of the operation.